Gut microbiota, hypertension and chronic kidney disease: Recent advances. (June 2019) - Sircana, Antonio; De Michieli, Franco; Parente, Renato; Framarin, Luciana; Leone, Nicola; Berrutti, Mara; Paschetta, Elena; Bongiovanni, Daria; Musso, Giovanni
Graphical abstract: Abstract: A large number of different microbial species populates intestine. Extensive research has studied the entire microbial population and their genes (microbiome) by using metagenomics, metatranscriptomics and metabolomic analysis. Studies suggest that the imbalances of the microbial community causes alterations in the intestinal homeostasis, leading to repercussions on other systems: metabolic, nervous, cardiovascular, immune. These studies have also shown that alterations in the structure and function of the gut microbiota play a key role in the pathogenesis and complications of Hypertension (HTN) and Chronic Kidney Disease (CKD). Increased blood pressure (BP) and CKD are two leading risk factors for cardiovascular disease and their treatment represents a challenge for the clinicians. In this Review, we discuss mechanisms whereby gut microbiota (GM) and its metabolites act on downstream cellular targets to contribute to the pathogenesis of HTN and CKD, and potential therapeutic implications.